Gambaran Pengetahuan Dan Sikap Perawatan Karies Gigi Pada Siswa Kelas XI Administrasi Perkantoran 2 SMK N 1 Kebumen - Putri Sukma Bitari; Quroti Ayun; Aryani Widayati (Poltekkes Kemenkes Yogyakarta, 2017)
Based on Riset Kesehatan Dasar Nasional (Riskesdas) in 2013, DMF-T index increased as the age goes by. Caries is the main cause of missing teeth among young people. This knowledge related to the people’s behavior about illness, preventive effort and also its treatment. The purpose of the study is to know the description knowledge and attitudes of students’ caries treatment in class XI of Office Administration 2 in SMK N 1 Kebumen. Method of the study was descriptive with crosssectional study design. This study had population that was all students of class XI Office Administration 2, withthe number of respondents was 36 students. The result showed that the description knowledge and attitudes of respondents’caries treatment were the middle category for level of knowledge with the number of respondents was 33 (91,67%), and the good category for positive attitude with the number of respondents was 34 (94,44%). Therefore, it can be concluded that knowledge and attitude of students’ caries treatment had been good.